Road safety game. - Four Square Stores (Australia) Pty. Ltd. ([Australia] : Four Square Stores (Australia) Pty. Ltd., 1960)
Designed to teach children road safety.
Promotional game introducing Four Square Stores (Australia) Pty. Ltd.
Board game.
"National Paper Ind. Pty Ltd.".
For children.
Also available online
Keywords: Board games -- Australia; Traffic safety -- Australia